High-Temperature Treatment to Improve the Capacity of LiBC Anode Material in Li-ion Battery - Yang, Qianwen; Chen, Langlang; Feng, Xiang; Li, De; Chen, Yong (Frontiers in Energy Research, 2020)
Being a graphite-like material, LiBC can deliver a high capacity as an anode material in Li-ion batteries, which are strongly dependent on carbon precursors. Developing a method to improve the capacity would be significant to the study and utilization of LiBC anode material. Here we treated a pristine LiBC material with a high temperature to obtain four modified LiBC samples. A reversible capacity of 353 mAh/g was delivered by a modified LiBC sample treated at 600°C for 10 h in a powder form wrapped with an Al foil, which was only 218 mAh/g for the pristine LiBC in Li-ion batteries. According to the XRD result, the layer structure of LiBC was maintained after the high-temperature treatment, while the lattice parameters were changed slightly, especially for the interlayer distance. The modified LiBC samples showed a similar Raman spectra to the pristine LiBC except for the peak intensity, which indicates lithium evaporation during high-temperature treatment. Thereby, the high-temperature treatment can improve the capacity of LiBC through reducing the lithium content and modifying the crystal structure, and this method would make the LiBC material become a more promising anode material in Li-ion batteries.